PENGARUH PROMOSI DAN PELAYANAN RITEL TERHADAP PEMBELIAN IMPULSIF DI RAMAYANA MALL MEDAN - MAJU SIREGAR (LP2MTBM MAKARIOZ, 2019)
The purpose of this study was to determine the effect of promotion and retail services to impulsive buying Ramayana Mall in Medan. This study used a qualitative research using surveys and questionnaires to 150 respondents visitors Ramayana Mall Medan. Sampling technique using non-probability sampling. The data analysis technique used in this study is multiple linear regression. It was found that the promotion variable positive and significant effect on impulsive buying Ramayana Mall in Medan and retail service variable positive and significant effect on impulsive buying Ramayana Mall in Medan.